Team-Based Integrated Knowledge Translation for Enhancing Quality of Life in Long-term Care Settings: A Multi-method, Multi-sectoral Research Design - Janice Keefe (International Journal of Health Policy and Management, 2020)
Multi-sectoral, interdisciplinary health research is increasingly recognizing integrated knowledge translation (iKT) as essential. It is characterized by diverse research partnerships, and iterative knowledge engagement, translation processes and democratized knowledge production. This paper reviews the methodological complexity and decision-making of a large iKT project called Seniors - Adding Life to Years (SALTY), designed to generate evidence to improve late life in long-term care (LTC) settings across Canada. We discuss our approach to iKT by reviewing iterative processes of team development and knowledge engagement within the LTC sector. We conclude with a brief discussion of the important opportunities, challenges, and implications these processes have for LTC research, and the sector more broadly.